Chasing graduate jobs? - Irene Mosca; Robert Wright (Institute for the Study of Labor (IZA), 2011)
This paper examines empirically the relationship between under-employment and migration amongst five cohorts of graduates of Scottish higher education institutions with micro-data collected by the Higher Education Statistical Agency. The data indicate that there is a strong positive relationship between migration and graduate employment - those graduates who move after graduation from Scotland to the rest of the UK or abroad have a much higher rate of graduate employment. Versions of probit regression are used to estimate migration and graduate employment equations in order to explore the nature of this relationship further. These equations confirm that there is a strong positive relationship between the probability of migrating and the probability of being in graduate employment even after other factors are controlled for. Instrumental variables estimation is used to examine the causal nature of the relationship by attempting to deal with the potential endogeneity of migration decisions. Overall the analysis is consistent with the hypotheses that a sizeable fraction of higher education graduates are leaving Scotland for employment reasons. In turn this finding suggests the over-education/under-employment nexus is a serious problem in Scotland.
urn:nbn:de:101:1-201203016214
Keywords: I23; J24; J61; R23; 330; Scotland; under-employment; over-education; higher education graduates; Akademiker; Unterbeschäftigung; Auswanderung; Schottland